Pain thresholds, supra-threshold pain and lidocaine sensitivity in patients with erythromelalgia, including the I848Tmutation in NaV 1.7 - Helås, Tormod; Schmelz, Martin (European journal of pain, 2017)
Objectives Nociceptive thresholds and supra-threshold pain ratings as well as their reduction upon local injection with lidocaine were compared between healthy subjects and patients with erythromelalgia (EM). Methods Lidocaine (0.25, 0.50, 1.0 or 10 mg/mL) or placebo (saline) was injected intradermally in non-painful areas of the lower arm, in a randomized, double-blind manner, to test the effect on dynamic and static mechanical sensitivity, mechanical pain sensitivity, thermal thresholds and supra-threshold heat pain sensitivity. Results Heat pain thresholds and pain ratings to supra-threshold heat stimulation did not differ between EM-patients (n = 27) and controls (n = 25), neither did the dose-response curves for lidocaine. Only the subgroup of EM-patients with mutations in sodium channel subunits NaV1.7, 1.8 or 1.9 (n = 8) had increased lidocaine sensitivity for supra-threshold heat stimuli, contrasting lower sensitivity to strong mechanical stimuli. This pattern was particularly clear in the two patients carrying the NaV 1.7 I848T mutations in whom lidocaine's hyperalgesic effect on mechanical pain sensitivity contrasted more effective heat analgesia. Conclusion Heat pain thresholds are not sensitized in EM patients, even in those with gain-of-function mutations in NaV1.7. Differential lidocaine sensitivity was overt only for noxious stimuli in the supra-threshold range suggesting that sensitized supra-threshold encoding is important for the clinical pain phenotype in EM in addition to lower activation threshold. Intracutaneous lidocaine dose-dependently blocked nociceptive sensations, but we did not identify EM patients with particular high lidocaine sensitivity that could have provided valuable therapeutic guidance. Significance Acute pain thresholds and supra-threshold heat pain in controls and patients with erythromelalgia do not differ and have the same lidocaine sensitivity. Acute heat pain thresholds even in EM patients with the NaV 1.7 I848T mutation are normal and only nociceptor sensitivity to intradermal lidocaine is changed. Only in EM patients with mutations in NaV 1.7, 1.8 or 1.9 supra-threshold heat and mechanical pain shows differential lidocaine sensitivity as compared to controls.